Corporate Governance and Firm Performance of Private Family Businesses in South Eastern Nigeria - Agbim, Kenneth Chukwujioke (International Journal of Economics, Business and Management Studies, 2019)
Research has shown that corporate governance mechanisms contribute to the sustainable growth of small, medium, large, private, public, listed and unlisted family firms in developed countries. However, in a developing country such as Nigeria, private family businesses are unprecedentedly becoming bankrupt and moribund, yet studies relating corporate governance to firm performance have not been sufficiently brought to the fore. Thus, this study seeks to investigate if the ownership structure and board structure contribute to the financial and non-financial performance of private family businesses that are incorporated as ‘limited liability’ firms in South Eastern Nigeria. The study adopted a qualitative methodology. The qualitative data were collated through interview. It was found that the private family businesses adopted family ownership and informally constituted board structures. Although family ownership influences financial and non-financial performance better than board structure, the adoption of family ownership and informal board structures together was found to better engender improvement in financial and non-financial performance. It is recommended that private family business owners be sensitized and trained on the relevance of ownership and board structures in achieving financial and non-financial performance. Again, such owners should be guided on how to implement these structures in their businesses.